Effector, Memory, and Dysfunctional CD8+ T Cell Fates in the Antitumor Immune Response - John Reiser; Arnob Banerjee (Journal of Immunology Research)
The adaptive immune system plays a pivotal role in the host’s ability to mount an effective, antigen-specific immune response against tumors. CD8+ tumor-infiltrating lymphocytes (TILs) mediate tumor rejection through recognition of tumor antigens and direct killing of transformed cells. In growing tumors, TILs are often functionally impaired as a result of interaction with, or signals from, transformed cells and the tumor microenvironment. These interactions and signals can lead to transcriptional, functional, and phenotypic changes in TILs that diminish the host’s ability to eradicate the tumor. In addition to effector and memory CD8+ T cells, populations described as exhausted, anergic, senescent, and regulatory CD8+ T cells have been observed in clinical and basic studies of antitumor immune responses. In the context of antitumor immunity, these CD8+ T cell subsets remain poorly characterized in terms of fate-specific biomarkers and transcription factor profiles. Here we discuss the current characterization of CD8+ T cell fates in antitumor immune responses and discuss recent insights into how signals in the tumor microenvironment influence TIL transcriptional networks to promote CD8+ T cell dysfunction.